Eating with a smaller spoon decreases bite size, eating rate and ad libitum food intake in healthy young males. Issue 7 (29th August 2018) - James, Lewis J.; Maher, Tyler; Biddle, Jack; Broom, David R.
Abstract: There is a paucity of data examining the effect of cutlery size on the microstructure of within-meal eating behaviour or food intake. Therefore, the present studies examined how manipulation of spoon size influenced these eating behaviour measures in lean young men. In study one, subjects ate a semi-solid porridge breakfast ad libitum, until satiation. In study two, subjects ate a standardised amount of porridge, with mean bite size and mean eating rate covertly measured by observation through a one-way mirror. Both studies involved subjects completing a familiarisation visit and two experimental visits, where they ate with a teaspoon (SMALL) or dessert spoon (LARGE), in randomised order. Subjective appetite measures (hunger, fullness, desire to eat and satisfaction) were made before and after meals. In study one, subjects ate 8 % less food when they ate with the SMALL spoon (SMALL 532 (SD 189) g; LARGE 575 (SD 227) g; P =0·006). In study two, mean bite size (SMALL 10·5 (SD 1·3) g; LARGE 13·7 (SD 2·6) g; P <0·001) and eating rate (SMALL 92 (SD 25) g/min; LARGE 108 (SD 29) g/min; P <0·001) were reduced in the SMALL condition. There were no condition or interaction effects for subjective appetite measures. These results suggest that eating with a small spoon decreases ad libitum food intake, possibly via a cascade of effects on within-meal eating microstructure. A small spoon might be a practical strategy for decreasing bite size and eating rate, likely increasing oral processing, and subsequently decreasing food intake, at least in lean young men.